Exploring the Nigerian transnational hotels' environmentally friendly practices towards biodiversity conservation in Lagos, Nigeria - Idoko, Ojochenemi; Kasim, Azilah (Open Access Publishing Group, 2019)
The increasing threat from excessive consumption of environmental resources is one of the leading factors responsible for environmental problems like deforestation, biodiversity reduction, ozone layer depletion, climate change, and global warming.Unfortunately, the hotel sub-sector of the tourism and hospitality industry is complicit in this regard. Previous studies have concentrated mainly on the environmental impact of hotel activities. Most studies on the environmentally friendly practice of hotels appear to be focusing more on the developed countries like the USA and the UK. A few developing countries in Asia continent like Malaysia, China, Thailand, Singapore, and Macao have also come under the limelight in recent times. But little is known about the involvement of Nigerian transnational hotels in biodiversity conservation regardless of the repeated calls for sustainability in the industry. This study attempts to explore how transnational hotel in Nigeria engage in biodiversity conservation. To accomplish this, data was collected through the in-depth interview from among the managerial staff in five transnational hotels in Lagos, Nigeria. Additionally, seven senior staff were purposively selected from among the regulatory and non-regulatory stakeholder of the hotel in Lagos state in order to have a balanced view on the study. NVivo 10 computer software was used to run a thematic analysis based on the transcribed interview data. It was revealed that only three of the hotels engages in some kind of biodiversity conservation practices. Based on the findings, the studies recommend that necessary policies be implemented by the relevant stakeholder to encourage environmentally friendly initiatives regarding biodiversity conservation. Also, the need for training and awareness creation regarding environmentally-friendly practices in the hotel as well as general environmental protection and management was advocated.